Bortezomib abrogates temozolomide-induced autophagic flux through an ATG5 dependent pathway - Rahman, Mohummad Aminur; Engelsen, Agnete S. T.; Sarowar, Shahin; Bindesbøll, Christian; Birkeland, Even; Goplen, Dorota; Lotsberg, Maria L.; Knappskog, Stian; Simonsen, Anne; Chekenya, Martha (Frontiers in Cell and Developmental Biology, 2022)
Glioblastoma (GBM) is invariably resistant to temozolomide (TMZ) chemotherapy. Inhibiting the proteasomal pathway is an emerging strategy to accumulate damaged proteins and inhibit their lysosomal degradation. We hypothesized that pre-treatment of GBM with bortezomib (BTZ) might sensitize glioblastoma to TMZ by abolishing autophagy survival signals to augment DNA damage and apoptosis. P3 patient derived GBM cells, as well as the cancer cell lines U87, HF66, A172, and T98G were investigated for clonogenic survival after single or combined treatment with TMZ and BTZ in vitro. We investigated the requirement of functional autophagy machinery by utilizing pharmacological inhibitors or CRISPR-Cas9 knockout (KO) of autophagy-related genes -5 and -7 (ATG5 and ATG7) in GBM cells and monitored changes in autophagic flux after TMZ and/or BTZ treatments. P3 wild-type and P3 ATG5-/- (ATG5 KO) cells were implanted orthotopically into NOD-SCID mice to assess the efficacy of BTZ and TMZ combination therapy with and without functional autophagy machinery. The chemo-resistant GBM cells increased autophagic flux during TMZ treatment as indicated by increased degradation of long-lived proteins, diminished expression of autophagy markers LC3A/B-II and p62(SQSTM1), increased co-localization of LC3A/B-II with STX17, augmented and no induction of apoptosis. In contrast, BTZ treatment abrogated autophagic flux indicated by the accumulation of LC3A/B-II and p62(SQSTM1) positive autophagosomes that did not fuse with lysosomes and thus reduced the degradation of long-lived proteins. BTZ synergistically enhanced TMZ efficacy by attenuating cell proliferation, increased DNA double-strand breaks, and apoptosis in an autophagy-dependent manner. Abolishing autophagy in ATG5 KOs reversed the BTZ-induced toxicity, rescued GBM cell death and reduced animal survival. We conclude that bortezomib abrogates temozolomide induced autophagy flux through an ATG5 dependent pathway.